O Biogás no Oeste do Paraná: potencialidade, desafios e perspectivas à luz da Nova Economia Institucional (NEI) - Strassburg, Udo (2016)
The aim of this study was to identify and analyze the institutional, organizational, technological, business, competitive and environment factors, which are influencing the agro-industrial system of biogas in western Paraná state (Brazil), due to the recycling activity of waste produced by the activities of pig farming. To reach the goal the following methodological procedures were used: hypothetical-deductive method and empirical and analytical research as working technique. Regarding the type of research, the study was descriptive, while the procedures used consisted in a field research (survey), the problem approach was qualitative. Finally the methodology used was the Discourse of the Collective Subject (DCS) method. A questionnaire with 25 open questions was applied to 14 leaders of the organizations involved in pig farming. The organizations surveyed are located in 10 municipalities most effective in pig farming in Western of Paraná. The theoretical framework is based on the New Institutional Economics - NIE, reporting to the model proposed by Farina, 1999. The description of the western Paraná state was realized by exposing its data on pig production. It was also presented biogas system, its origin, and characteristics, how it appears in the Brazilian and world energy matrix, highlighting as it shows the environment, the institutional environments, competitive, business, organizational and technological of its system. After, the view of related organizations with pig production and the consequent production of biogas in western Paraná was exposed. The agro-industrial system of biogas in the Western of Paraná state is in its early stage, and it has a good way still to go. At the institutional scope can be highlighted the Resolução Normativa ANP nº 8/2015 (a Brazilian Normative Resolution presented by the National Agency of Petroleum, Natural Gas and Biofuels ANP), as the resource that will support the system. Organizations linked to biogas in Western Paraná state have few contributions with regard to biogas; they have not acted together, leaving to join forces to progress. In the technological environment it was found that there needs to develop advances for use in small farms, which are prevalent in the study environment, missing prove that this technology is sufficient and that can give some return for the activity. Regarding the competitive environment was found that biogas is still not a product it has market. The transactions do not exist, bringing many uncertainties and mistrust of information provided. With the environment there is a constant concern, even so the producer makes a logical connection, stating that there is a need for return on investment.